2007
DOI: 10.1080/00016340701692651
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum hysterectomy in Denmark 1995–2004

Abstract: Peripartum hysterectomy has increased significantly during the last 20 years. Optimizing treatment of PPH may decrease the incidence of peripartum hysterectomy in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 16 publications
7
54
2
3
Order By: Relevance
“…This incidence was higher than what has been reported in Durban in South Africa of 5.1/1000 3 and in Southern Nigeria of 5.4/1000 1 and in Ghana of 4.3/1000 2 . This incidence was much higher than what has been reported in developed countries which are below 1/1000 births 9,14 . The difference between NMAH and Durban can be attributed to the differences in the level of obstetric care offered.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…This incidence was higher than what has been reported in Durban in South Africa of 5.1/1000 3 and in Southern Nigeria of 5.4/1000 1 and in Ghana of 4.3/1000 2 . This incidence was much higher than what has been reported in developed countries which are below 1/1000 births 9,14 . The difference between NMAH and Durban can be attributed to the differences in the level of obstetric care offered.…”
Section: Discussioncontrasting
confidence: 61%
“…In United Kingdom it is 0.41/ 1000 births 7 , Denmark it is 0.24/1000 births 9 , in Saudi Arabia it is 0.64/1000 10 , in Korle Bu Ghana it is 4.34/1000 2 , Nigeria 5.4/1000 1 and Durban in South Africa 5.1/1000. 3 The differences have been attributed to the different levels of obstetric care offered.…”
Section: Introductionmentioning
confidence: 99%
“…5 Previous studies in the literature have reported the incidence of EPH varies from 0.29 to 5.09 per 1000 deliveries. [6][7][8] Indications for peripartum hysterectomy have changed throughout the years. In the past, the major indications for EPH were uterine rupture and atony.…”
Section: Introductionmentioning
confidence: 99%
“…In modern obstetrics, the overall incidence of EPH is 0.05%, but there are considerable differences in incidence in different parts of the world, depending on modern obstetric services, standards and awareness of antenatal care, and the effectiveness of family planning activities of a given community [6]. The incidence of peripartum hysterectomy in the literature is reported as 0.24, 0.77, 2.3, and 5.09 per 1,000 deliveries by Sakse et al [7], Whiteman et al [8], Bai et al [9] and Zeteroglu et al [10], respectively. However, there is a lack of Portuguese data on EPH.…”
Section: Introductionmentioning
confidence: 99%